Information security practice and experience : 12th International Conference, ISPEC 2016, Zhangjiajie, China, November 16-18, 2016, Proceedings /: 12th International Conference, ISPEC 2016, Zhangjiajie, China, November 16-18, 2016, Proceedings. (2016) - Unknown
No abstract available